ASSESSMENT OF SEXUAL BEHAVIOR AND KNOWLEDGE ABOUT HIV BY AGE AND SEX IN HIGH SCHOOL STUDENTS IN ELBASAN, ALBANIA - Krasniqi, Marsida (European Scientific Journal, ESJ, 2014)
In this study the sexual behavior and knowledge about HIV isanalyzed by age and sex among high schools students. A cross-sectionalstudy has involved 474 students aged between 15-20 years old in eight publichigh schools in Elbasan; the selection of the students was done randomized.Students have completed a questionnaire about sexual behavior, informationthat had about HIV and about the information source. Results showed thatstudents in addition to accurate information about HIV, reported wronginformation about HIV transmission. Not an appropriate sexual behavior wasseen with high frequency among students, especially in the age group 15-16years old. It was noted that information received about HIV among studentswas influenced by TV, Internet, and by friends. In conclusion we can say thatshould be made specific interventions to students, especially in the age group15-16 years old in order to prevent new HIV infections.